2010
DOI: 10.1016/j.molcel.2010.09.019
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Damage Response: Making It Safe to Play with Knives

Abstract: Damage to our genetic material is an ongoing threat to both our ability to faithfully transmit genetic information to our offspring as well as our own survival. To respond to these threats, eukaryotes have evolved the DNA Damage Response (DDR). The DDR is a complex signal transduction pathway that has the ability to sense DNA damage and transduce this information to the cell to influence cellular responses to DNA damage. Cells possess an arsenal of enzymatic tools capable of remodeling and repairing DNA, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
3,960
3
43

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 3,741 publications
(4,045 citation statements)
references
References 247 publications
(381 reference statements)
39
3,960
3
43
Order By: Relevance
“…cDNA pool prepared from the previous reaction was diluted by Activated checkpoints not only induce cell cycle arrest or cell death in response to some types of DNA damage (Nakano and Vousden, 2001;Yu et al, 2001) but also shown to protect tumour cells from apoptosis (Meuth, 2010;Rodriguez and Meuth, 2006;Sidi et al, 2008). In eukaryotic cells there are two highly conserved signalling cascades: two members of the phosphatidylinositol 3-kinase-like family of kinases, Ataxia telangiectasia mutated (ATM) and ATM and Rad3 related (ATR) (Ciccia and Elledge, 2010) participate in these systems. Under DNA damage or replication stress, these activated kinases phosphorylate a number of downstream proteins to protect DNA integrity, including two key protein kinases, checkpoint kinase 1 (CHK1) and checkpoint kinase 2 (CHK2) (Bartek and Lukas, 2003).…”
Section: Qpcrmentioning
confidence: 99%
“…cDNA pool prepared from the previous reaction was diluted by Activated checkpoints not only induce cell cycle arrest or cell death in response to some types of DNA damage (Nakano and Vousden, 2001;Yu et al, 2001) but also shown to protect tumour cells from apoptosis (Meuth, 2010;Rodriguez and Meuth, 2006;Sidi et al, 2008). In eukaryotic cells there are two highly conserved signalling cascades: two members of the phosphatidylinositol 3-kinase-like family of kinases, Ataxia telangiectasia mutated (ATM) and ATM and Rad3 related (ATR) (Ciccia and Elledge, 2010) participate in these systems. Under DNA damage or replication stress, these activated kinases phosphorylate a number of downstream proteins to protect DNA integrity, including two key protein kinases, checkpoint kinase 1 (CHK1) and checkpoint kinase 2 (CHK2) (Bartek and Lukas, 2003).…”
Section: Qpcrmentioning
confidence: 99%
“…As is known, DNA repair after radiation is an important mechanism of radioresistance 33, 34. Considering that bioinformatic prediction has become a preferential method to explore the targets of miRNAs,35, 36 we chose potential targets from predicted ones involved in radioresistance and confirmed these targets by biochemical experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Physical and biochemical repair of radiation induced DNA damage is executed by three main pathways: non-homologous end-joining (NHEJ) and homologous recombination (HR), which repair double stranded DNA breaks (DSB); and base excision repair (BER), which repairs single stranded DNA breaks (SSB) (reviewed in [3]). In the context of conventional external beam radiotherapy, DSB are generated in far fewer numbers than SSB but are highly mutagenic, and are cytotoxic if unrepaired.…”
Section: Introductionmentioning
confidence: 99%